Corrosion of steel piles - Law, Kong Hoi. (2008)
This dissertation comprises mainly of three sections; namely, a literature review and two case studies. In the literature review, a summary of the various types of corrosion of steel piles, the corrosion mechanisms and soil corrosivity was included.